Persistent disparities in breast cancer surgical outcomes among hispanic and African American patients. Issue 4 (April 2019) - Mets, Elbert J.; Chouairi, Fouad K.; Gabrick, Kyle S.; Avraham, Tomer; Alperovich, Michael
Abstract: Background: Racial disparities among patients who receive breast mastectomy and reconstruction have not been well characterized. Methods: Records of patients undergoing breast extirpative and reconstructive surgery at a high-volume university-affiliated hospital over 5 consecutive years were reviewed. Patient demographics, breast cancer profiles, reconstructive modality, and outcomes were compared by race. Results: A total of 1045 patients underwent 1678 breast reconstructions during the five-year period. Mean age and standard deviation was 49.8 ± 10.6 years with a BMI of 27.9 ± 6.5. Hispanic and African American patients had significantly higher BMIs (p < 0.001), higher rates of ASA class III or IV (p = 0.025), obesity, diabetes, hypertension (p < 0.001 for these three comparisons), and smoking (p = 0.003), and had more prior abdominal surgeries (p = 0.007). Comparing oncologic characteristics, this population subset had higher rates of neoadjuvant chemotherapy (p = 0.036), history of radiation (p = 0.016), and were more likely to undergo modified radical mastectomy (p = 0.002) over nipple-sparing mastectomy (p = 0.035). Reconstructive complications revealed a higher overall complication rate (p = 0.023), higher rates of partial mastectomy flap necrosis (p = 0.043), as well as arterial (p = 0.009) and venous insufficiency (p = 0.026) during microvascular reconstruction among Hispanic and African American patients. Conclusions: Compared to other patients, the present study identifies higher comorbidity burdens, higher rates of prior radiation and neoadjuvant chemotherapy, and higher post-surgical complication rates among Hispanic and African American patients with breast cancer.